Headmasters' understanding and readiness in implementing Zero Reject Policy at primary schools in Selangor, Malaysia - Che Mat, Hanizan (2023)
Malaysia has a long history of providing education for children with special needs. Special education in the country is governed by the Malaysia Education Blueprint 2013- 2025, which aims to improve access and inclusiveness among all schools in the country. This study aimed to study headmasters' understanding and readiness in implementing a newly rebranded policy introduced by the Ministry of Education Malaysia. The study adapted a phenomenology design that involved six headmasters of primary schools in Selangor who were chosen from purposive sampling based on inclusion and exclusion criteria sets. The study was guided by two research questions: (1) To what extent do the headmasters of primary schools in Selangor understand the implementation of the Zero Reject Policy (ZRP)? and (2) How ready were the headmasters of primary schools in Selangor to implement the ZRP? Three qualitative data collection methods were used which include semi-structured interviews, document analysis, and observation. Data collected was analysed by using ATLAS.ti (Version 9) software and five themes emerged from the analysis. The study found that most headmasters understand the objectives of the ZRP in providing access to education. However, issues such as poor infrastructure have presented a big challenge for headmasters to properly implement the policy. The data revealed that the headmasters demanded more knowledge on special education during their leadership preparation program. The impact of the policy showed that the headmasters gained knowledge on special education however, schools became more crowded with special educational needs students. The study concludes that the implementation of ZRP has challenged headmasters in three different perspectives, which are awareness, leadership skills, and access to education. The ZRP requires parents and teachers to have a good relationship to promote the right to education for all special education needs children, regardless of their background, location, and socioeconomics.